Conception of logistics coordination in the distribution networks - Mariusz Kmiecik (Logistics Research, 2022)
The main aim of following research paper is the definition of logistics coordination in the distribution network. Research paper also is aimed on distinguishing the further research steps. Research methodology focuses on the problematic of literature review in the conditions of coordination, distribution network central nodes, coordination mechanisms and occurring in the literature the phases connected with logistics coordination. Literature review allows to elaborate the logistics coordination concept in the distribution networks and sowing the further research steps in this area. Logistics coordination is occurred in the literature, but it is understood differently than following paper assumed. Author tried to define the logistics coordination and to distinguish the main elements which have influence on it. Among the most important elements which have influence of logistics coordination were mentioned factors as: actions of contemporary logistics operators, market, social and hierarchic mechanisms of network coordination, the opportunity of reaching by operators the function of demand management and possibility of usage the modern technical achievements connected with data interchange. Established elements of logistics coordination could help logistics operator in the tray of adaptation of this function in distribution networks. Among that function there worth be mentioned benefits like decreasing the stocks level, better resource and stocks allocation, reduction of logistics activity costs, increasing the customer satisfaction level, increasing the activities flexibility by coordination directed to material and information flows management. Additionally, the main distinguishing feature of this conception is the fact of logistics operator don't have the direct revenues from sales, which could also reduce the possibility of unplanned promotional actions and its influence of whole network. Logistics coordination could be defined as the activity coordination which is connected with flows management which is done by logistics operator in the area of current actions, actions connected with demand management, usage of nowadays information technologies market, social and hierarchic network coordination mechanism point of view.
Keywords: 650; 3PL; coordination; distribution network; logistics coordination; logistics operator; third-party logistics